Evaluasi Pengerjaan Detailing Tulangan pada Komponen Struktur Beton Bertulang Pembangunan Rumah Sederhana di Wilayah Kabupaten Bandung - Gunawan, Johanna; Kristianto, Anang (Jurnal Teknik Sipil, 2024)
When carrying out a simple house construction project, it is crucial to assess the implementation of reinforcing bar detailing for reinforced concrete structural components, as field errors often occur. Inaccuracies in the installation of such reinforcing bar detailing can lead to a decrease in the quality of the house, affecting its earthquake resistance. Based on this, the installation of reinforcing bar detailing must adhere to the applicable standards, namely SNI 2847-2019, SNI 8900-2020, and guidelines issued by the Ministry of Public Works and Public Housing. The evaluation of the construction is obtained through a literature review method in line with field case studies. Field observations result in a depiction of errors in the reinforcing bar detailing, such as foundation cutting errors, incorrect stirrup spacing, stirrup bending errors, and the length of reinforcing bar placement in structural elements. Therefore, the reinforcing bar detailing work must be redone and reorganized according to the prevailing standards.